Colour image encryption algorithm using one‐time key and FrFT. Issue 4 (1st April 2018) - Gao, Zhenguo; Chen, Danjie; Zhang, Wei; Cai, Shaobin
Abstract : A novel chaos‐based colour image encryption algorithm is proposed, which adopts a one‐time key mechanism based on message‐digest algorithm 5 (MD5 ) value of the input plain image. The algorithm combines several key technologies including fractional Fourier transform (FrFT), MD5, and global scrambling. Using fast digital discrete FrFT, the algorithm develops the complex data manipulating potentials of FrFT efficiently; meanwhile, keeps the size of the cipher image un‐changed, thus eliminates the requirement on double storage space to store complex values of cipher image. Exploiting the intrinsic robustness of FrFT, the algorithm achieves high robustness to pixel errors and noise attacks. Experimental results show that the algorithm achieves better pixel change rate and unified average change intensity, and is efficient, effective, and robust to attacks.